ANALISIS EFEKTIVITAS PEMUNGUTAN PAJAK PENJUALAN ATAS BARANG MEWAH TERHADAP PENERIMAAN PAJAK DI KPP PRATAMA MANADO - Sorongan, Fenny Fega Stela; Kalangi, Lintje; Tangkuman, Steven (Universitas Sam Ratulangi, 2015)
Along with economic development , information technology , social , political , realized that the implementation of the taxation system in Indonesia requires a provision and good manners. Sales Tax on Luxury Goods is a type of tax potential in the reception area is well to state. The object of this study was taken at the Tax Office Primary Manado , to determine the performance of the 2011-2014 effective or less effective. It can be in anlisa on performance Pratama Tax Service office Manado. The purpose of this study was to determine the effectiveness of the collection of Sales Tax on Luxury Goods on receipt. Data that has been processed and analyzed using qualitative descriptive analysis research method. The results of the study addressed that the payment procedure in terms of voting to taxpayer is right in accordance with the law. So level of performance Partama Manado Tax Office Effectively , there are even a few years of very effective . However, the performance should be increased for a given target is no change the decrease in one year, although its realization is achieved. That should have been the target increases each year as well as its realization. Thereby acchieving Performance KPP Pratama Manado can be said effective.